الجرعات الإشعاعية الناتجة عن الهاتف الخليوي - العلي, علي محمود (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن البحث الراهن عرضاً مختصراً لمشكلة الحماية من إشعاعات الحقل الكهرطيسي غير المؤين. وفي هذا المجال نقدم إحدى الطرق المتطورة " النمذجة الرقمية للحقل الكهرطيسي " , والتي تسمى بطريقة الفروقات المنتهية بالزمن(FDTD ) . تهدف هذه الطريقة لمعالجة مشكلة قياس الجرعات الإشعاعية الناتجة عن الهاتف الخليوي ,التي توصلنا بنتيجتها إلى نتائج رقمية سيتم عرضها بوصفها أمثلة وبراهين . This research includes the problem of protection against the none-ionized electro-magnetic field radiation. In this respect, we highlight one of the advanced methods "digital simulation of the electric field", which is called the Finite Difference Time Domain method (FDTD). This method aims at solving the problem of measuring the radiation dosages produced by the cellular (phone). Therefore, we have got numerical mathematical results to be presented as proofs and examples.